2017
DOI: 10.3233/bsi-170171
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy as a new tool for studying single living cells: Is there a niche?

Abstract: Abstract. FTIR spectroscopy is an analytical technique widely applied for studying the vibrational fingerprint of organic compounds. In recent years, it has been applied to many biomedical fields because of its potential to detect the composition and molecular structure of various biological materials without the need of probe molecules. The coupling of IR spectrometers with visible microscopes has led to perform the imaging analysis of non-homogeneous samples, such as tissues and cells, in which the biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 74 publications
0
46
0
Order By: Relevance
“…It was found that the water uptake was enhanced from 277 ± 22% for the PEUUF scaffold to 367 ± 5% for the PRP-PEUUF ones. The FTIR-ATR analysis of those PRP-PEUUF scaffolds presented the significant bands of PEUUF, and also exhibited bands from proteins present in PRP, such as the amide I and II groups of the peptide bond at respectively, 1650 cm −1 and 1542 cm −1 , the bending of CH 2/3 groups present in amino acid side chains at 1400 cm −1 , as well as the broadening of the band centered at 3293 cm −1 assigned to the protein NH groups (Figure 7) [45].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the water uptake was enhanced from 277 ± 22% for the PEUUF scaffold to 367 ± 5% for the PRP-PEUUF ones. The FTIR-ATR analysis of those PRP-PEUUF scaffolds presented the significant bands of PEUUF, and also exhibited bands from proteins present in PRP, such as the amide I and II groups of the peptide bond at respectively, 1650 cm −1 and 1542 cm −1 , the bending of CH 2/3 groups present in amino acid side chains at 1400 cm −1 , as well as the broadening of the band centered at 3293 cm −1 assigned to the protein NH groups (Figure 7) [45].…”
Section: Resultsmentioning
confidence: 99%
“…The discerned peak at 1686 cm −1 can be attributed to the stretching band of CO, which was attached to the aromatic ring of hydroxyproline and proline proteins in the collagen type I structure. The triple helical structure of collagen type I is typically characterized by the absorbance peak at 1637 cm −1 . The peaks at 1650 and 1540 cm −1 can be assigned to the amide‐type I and amide type II, which can be related to the vibration of peptide bonds (stretching modes of CO and CN, and bending mode of NH).…”
Section: Resultsmentioning
confidence: 99%
“…FTIR spectroscopy has been demonstrated to be an effective and non-invasive diagnostic method that characterizes the biochemical changes in tissues, cells, and even at the molecular level [ 8 ]. Oligodendroglial and astrocytic tumor cells can easily be identified by their infrared spectra, with characteristic features in the lipid acyl chain region as well as in the nucleic acid region [ 9 , 10 ]. For glioblastoma stem cells, attenuated total reflection (ATR) FTIR spectroscopy allows correct classification of the tissues, differentiating between CD133-rich and CD133-poor populations [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%